Late Cretaceous extension and exhumation of the Stong and Taku magmatic and metamorphic complexes, NE Peninsular Malaysia. (1st August 2017) - François, T.; Md Ali, M.A.; Matenco, L.; Willingshofer, E.; Ng, T.F.; Taib, N.I.; Shuib, M.K.
Graphical abstract: Highlights: Understanding the mechanics of post-orogenic extension in SE Asia. Late Cretaceous detachment in the northern Peninsular Malaysia. High-temperature extensional deformation and syn-kinematic magmatism. Exhumation of the previously buried Indosinian suture by extension. The research suggests a thermal anomaly triggering an extensional gneiss dome. Abstract: Fragmentation of large continental areas by post-orogenic extension requires favourable geodynamic conditions and frequently occurs along pre-existing suture zones or nappe contacts, as exemplified by the Stong and Taku magmatic and metamorphic complexes of northern Peninsular Malaysia. For this case, we have employed a field and microstructural kinematic study combined with low temperature thermo-chronology to analyse the tectonic and exhumation history. The results show that the Late Palaeozoic - Triassic Indosinian orogeny created successive phases of burial related metamorphism, shearing and contractional deformation. This orogenic structure was subsequently dismembered during a Cretaceous thermal event that culminated in the formation of a large scale Late Santonian - Early Maastrichtian extensional detachment, genetically associated with crustal melting, the emplacement of syn-kinematic plutons and widespread migmatisation. The emplacement of these magmatic rocks led to an array of simultaneously formed structures that document deformation conditions over a wide temperature range, represented by amphibolite- and greenschist- facies mylonites and as well as brittle structures, such as cataclastic zones and normal faults that formed during exhumation in the footwall of the detachment. The formation of this detachment and a first phase of Late Cretaceous cooling was followed by renewed Eocene - Oligocene exhumation, as evidenced from our fission track ages. We infer that an initial Cretaceous thermal anomaly was responsible for the formation of an extensional gneiss dome associated with simple shear and rotation of normal faults. These Cretaceous processes played a critical role in the establishment of the presently observed crustal structure of Peninsular Malaysia.